Field evaluation of tissue culture-derived and offshoot-grown date palm cultivars: a comparative analysis of vegetative and fruit attributes - Solangi, Najamuddin; Mirani, Abdul Aziz; Jatoi, Mushtaque Ahmed; Abul-Soad, Adel Ahmed; Bhanbhro, Lal Bux; Markhand, Ghulam Sarwar; Hedayat, Mohammad; Abdi, Gholamreza (Frontiers in Plant Science, 2025)
An analysis of the field performance of tissue culture (TC)-derived commercial cultivars of date palm (i.e., Kashuwari, Gulistan, and Dedhi) obtained from juvenile inflorescence explants was carried out to compare the different vegetative and fruit attributes with their respective offshoot (OS)-grown mother plants. A comparative analysis of leaf-, bunch-, and fruit-related variables was conducted 5 years after planting in an open field. The data obtained were used to perform ANOVA, k-means clustering, and principal component analysis (PCA). The results revealed that the majority of the variables showed non-significant variations between TC plants and OS-grown mother plants across all three cultivars. K-means clustering produced three distinct clusters for each of the three cultivars, placing all their TC and OS plants together in their respective clusters, except for one TC plant of cv. Gulistan, which was placed with cv. Dedhi. The PCA results showed that the first two components explained a significant proportion of the total variation in all three date palm cultivars, ranging from 71.4% to 76.4%. This study provides critical insights for the validation of TC methods, assessing adaptability under open field conditions, ensuring genetic stability, and ultimately expanding the adoption and impact of TC techniques in agriculture.